Human menopausal gonadotropin-induced bioprosthetic valve thrombosis - Abazid, Rami Mahmood; Shoman, Mohamed; Smettie, Osama A; Elamin, Osama A. (Avicenna Journal of Medicine, 2018)
Bioprosthetic valve thrombosis (BPVT) is a rare but potentially life-threatening complication. Human menopausal gonadotropin (hMG) is commonly used for ovulation induction and has been associated with arterial and venous thrombosis. We reported a case of BPVT related to in vitro fertilization in a 39-year-old female, who underwent redo mitral valve replacement. To the best of our knowledge, this is the first case of hMG-induced BPVT in a young female patient.
Keywords: Bioprosthetic valve thrombosis; human menopausal gonadotropin; in vitro fertilization